CARDIAC REHABILITATION: TRENDS IN MEDICARE UTILIZATION AND REIMBURSEMENT - Khan O. Mohammad; Charles Hyman; George Rodgers; Clay Cauthen (Elsevier, 2023)
Therapeutic Area: Rehabilitation Background: Intensive cardiac rehabilitation is an AHA/ACC class 1 recommendation following coronary intervention as it has been shown to be an excellent modality in modifying cardiovascular risk factors following an acute myocardial event. However, trends in utilization and procedural reimbursement for cardiac rehabilitation services remain unevaluated. Methods: Publicly available data from the Centers for Medicare and Medicaid database were utilized for all years, 2013-2019, for which data was available. Evaluation was limited to Medicare Part B beneficiaries that were enrolled solely in the Medicare 'fee-for-service' plan. Using the Healthcare Common Procedure Coding System (HCPCS), the number of patients that underwent percutaneous coronary intervention (PCI) or coronary artery bypass grafting (CABG) was compared with the number of patients that underwent cardiac rehabilitation. The HCPCS codes analyzed were: 33533-33536 for CABG, 92920-92944 for PCI, G0422-G0423 for intensive cardiac rehabilitation and 93797-93798 for outpatient cardiac rehabilitation. Results: In 2019, 194,754 Medicare Part B beneficiaries underwent coronary intervention but only 21,628 were enrolled in some form of cardiac rehabilitation (11.1%). This is an increase from 2013 when 183,685 Medicare Part B beneficiaries underwent coronary intervention and only 17,430 were enrolled in cardiac rehabilitation (9.5%). These rates indicate that cardiac rehabilitation is still tremendously underutilized. Medicare reimbursement limits for intensive cardiac rehabilitation have risen from $79.95 per beneficiary/day in 2013 to $118.21 per beneficiary/day in 2019 - a 34.4% increase when adjusted for inflation. However, the average Medicare payment received per beneficiary/day for cardiac rehabilitation was $60.72 in 2013 and $93.17 in 2019 - a 39.4% increase when adjusted for inflation. Conclusions: Cardiac rehabilitation continues to be an extremely underutilized modality of decreasing cardiovascular risk factors following coronary intervention. While potential Medicare reimbursement is increasing for these services, the actual amounts lag behind.